(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Inferile males have been shown to have lower levels of seminal plasma zinc which have been associated with reduced levels of zinc in their blood. Supplementation improve semen parameters by improving zinc level in blood. Objective: To fnd out whether zinc supplementation is effective in improving semen parameters in oligoasthenozoospermic patients. Method: The study was carried out in the Infertility unit of the Dept of Obs & Gynae, BSMMU during the period of March 2011 to February 2012. Seventy five oligo-asthenozoospermic patients having no history of medical treatment were recruited for the study. The patients were divided into two groups by odd and even numbers. Odd numbers received tablet zinc 20 mg twice daily (Group A) and even numbers received placebo (Group B).Serum zinc level and seminal zinc level estimation were done by Graphite Furnace Atomic Absorption Spectrophotometry and semen analysis was done according to WHO guidelines (1999). Data analysis was done using software SPSS (version 16) by applying ANOVA (PostHock) and Paired Student’s ’t’ test. Results: Serum zinc level was low in oligozoospermic patients which showed significant improvement with zinc supplementation (A+ 197.83 mmol/1, P<0.01). Mean (±SD) seminal plasma zinc level showed significant improvement in group A following zinc supplementation (+942.39 mmol/L, P<0.001). The mean increase in sperm count, sperm motility, sperm rapid linear motility, sperm morphology in group A following zinc supplementation for 12 weeks was 14.83 million/ml (P<0.01), 16.30% (P<0.01), 11.96% (P<0.01), 4.26% (P<0.001) respectively, which was statistically significant. Conclusion: The study shows zinc deficiency affects sperm count, sperm motility, rapid linear motility and sperm morphology and with zinc supplementation there can be significant improvement in semen parameters.